2008
DOI: 10.1002/pola.22841
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of norbornene with a pendent sulfonyl fluoride group catalyzed by palladium complex bearing tBu3P ligand

Abstract: The combination of palladium complex (tBu3P)Pd(Me)Cl (1) and NaB[3,5‐(CF3)2C6H3]4 (NaBAr4) catalyzed homopolymerization of a novel monomer, norbornene (NB) with a pendent 2‐fluorosulfonyltetrafluoroethoxymethyl chain (NBSF). Catalytic activities of 1/NaBAr4 were higher than those of previously reported palladium or nickel catalysts, probably, because the palladium center with electron donative tBu3P ligand was barely poisoned by the sulfonyl fluoride coordination. Thus, 1/NaBAr4 is the current best catalyst sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…From the above equation, x could be calculated as 10By/(A‐5B), and the NBMOH content is calculated to be about 6.85% 23. It is indicated that there is about 6.85% of NBMOH in the copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…From the above equation, x could be calculated as 10By/(A‐5B), and the NBMOH content is calculated to be about 6.85% 23. It is indicated that there is about 6.85% of NBMOH in the copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…The contents of 1‐hexene or 1‐octene in copolymers were calculated by the following literature method 1‐alkene (mol%)=InormalCH3+InormalCH2InormalC2/C3+InormalCH3+InormalCH2 where I CH3 and I CH2 represents the area of the methyl and methylene in the branched chain end of 1‐hexene or 1‐octene region respectively and I C2/C3 represents the area of the position C2 and C3 methine of norbornene.…”
Section: Resultsmentioning
confidence: 99%
“…2, the peaks at 0.9-1.0 ppm could be assigned to the hydrogen corresponding to 6′, the peaks at 1.0-1.5 ppm could be assigned to the hydrogen corresponding to 4/5/7/1′/3′/4′/5′, the peaks at 1.6-1.9 ppm could be assigned to the hydrogen corresponding to 3/6 and the peaks at 2.1-2.5 ppm could be assigned to the hydrogen corresponding to 1/2/2′, respectively. The content of 1-hexene in copolymers (see Table 1) could be calculated [39] and were (a) 9.2 %, (b) 20.1 %, (c) 25.3 %. Meanwhile, in Fig.…”
Section: H and 13 C Nmr Spectra Of The Copolymersmentioning
confidence: 99%